Synergistic influences of ground granulated blast-furnace slag and silica fume on the viscosity of extremely low W/B cement pastes - Nguyen, Cong Thang; Phung, Quoc Tri; Nguyen, Van Tuan (Vietnam Journal of Science and Technology, 2024)
Particularly with a low water/binder ratio, the synergistic effects of supplemental cementitious materials (SCMs) have drawn a lot of interest in improving the characteristics of cement-based products. The effects of SCMs, such as silica fume (SF) and ground granulated blast furnace slag (GGBS) with varying fineness, on the setting time, saturation point, and viscosity of ultra-high performance cement pastes (UHPCP), are examined experimentally in this work. 56 mixes with various SF and BFS substitutions and exceptionally low water/binder ratios (0.16, 0.20) were used in the experiments. This work demonstrates the synergistic effects of SCMs from several angles, including the UHPCP fresh characteristics. It is shown that carefully regulating the water/binder ratio, the BFS fineness, and most significantly the addition of an ideal SF content will have a beneficial synergistic effect on the fresh qualities of UHPCP. However, utilizing high BFS replacement is discouraged as it may have a negative impact on viscosity.